Implementation of Effective Communication For The Preparation of Oral Presentation Nursing Students at STIKES Bina Sehat PPNI Mojokerto - Zainudin, Moh; Munfadlila, Asef Wildan (STRADA : Jurnal Ilmiah Kesehatan, 2021)
Oral presentation preparation material as one of the materials to hone speaking skills is very important to be mastered by students. The objectives of this study were: 1) To describe the effective communication preparations for the oral presentation preparation material for the Nursing Undergraduate students of STIKES Bina Sehat PPNI Mojokerto. 2) Describe the results of the implementation of effective communication of the oral presentation preparation material for the Nursing Undergraduate students of STIKES Bina Sehat PPNI Mojokerto. This research method uses qualitative research methods with the number of data sources as many as 40 undergraduate nursing students. The data collection technique used by the researcher was the assignment sheet. The results of this study indicate that all students are able to make effective communication preparations with interesting and actual topics, and are able to apply effective communication stages well